Educational Management At Harapan Mandiri Private Elementary School in Medan - Jainab Jainab; Srie Faizah Lisnasari; Eti Muliani; Juwita Tindaon (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
School should be run with good management in order to reach goal related to the management of the educational process to achieve the goals set, both short term, medium term and long term goals. The purpose of this study was to describe a method of instilling multicultural values in students aged 8-9 years or more precisely, sitting in grade 2 of elementary school at Harapan Mandiri Private Elementary School in Medan. This research method uses qualitative research methods with the type of field research (field research), data collection using observation (observation) and interviews. The results showed that the implementation of Planning, Organizing, Implementation and Supervision of Multicultural Education at Harapan Mandiri Private Elementary School in Medan City went well. The learning that is applied by the teacher in its implementation by providing understanding and then being practiced, indirectly helps the formation of good morals for students in everyday life which is exemplified in the school environment. Obstacles in the field such as the lack of storytelling media/techniques used by teachers, the inconsistency of student behavior at school, at home and in the neighborhood. Efforts are being made to overcome this by holding regular meetings with parents/guardians for a certain period of time continuously in order to the learning more sustainable.